Kiwifruit bacterial canker in Hayward kiwifruit Design of a quantitative questionnaire for kiwifruit growers - Froud, K.J.; Cogger, N.; Beresford, R.M. (New Zealand Plant Protection, 2016)
Longer term effects of Pseudomonas syringae pv actinidiae biovar 3 (Psa) on Hayward kiwifruit (Actinidia chinensis var deliciosa) production are unclear and there is uncertainty about what impact orchard activities could have on disease prevalence The aim of the present study was to determine the validity of the data obtained from a crosssectional observational study using a quantitative postal questionnaire on disease and risk factor prevalence from commercial growers of Hayward The questionnaire was sent to 1669 growers and 442 responded (26) a response rate similar to that of other agriculture surveys in New Zealand Nonresponses were analysed against a range of factors to assess response bias There was a higher response rate from organic growers and those affiliated with specific packhouses There were no differences between responders and nonresponders according to the period of time their orchard had been infected with Psa or to orchard productivity We conclude that a postal questionnaire was an effective way to obtain quantitative disease risk factor and hygiene data from commercial producers